2010
DOI: 10.1111/j.1529-8817.2010.00934.x
|View full text |Cite
|
Sign up to set email alerts
|

ORGANIC CARBON SUPPLEMENTATION OF STERILIZED MUNICIPAL WASTEWATER IS ESSENTIAL FOR HETEROTROPHIC GROWTH AND REMOVING AMMONIUM BY THE MICROALGA CHLORELLA VULGARIS1

Abstract: Heterotrophic growth of the microalga Chlorella vulgaris Beij. in synthetic as well as sterilized municipal wastewater of a nonindustrialized city was measured. The city wastewater contained high levels of ammonium and nitrate, medium levels of phosphate, and low levels of nitrite and organic molecules and could not support heterotrophic growth of C. vulgaris. Evaluation of 11 known carbon sources for this microalga that were added to standard synthetic wastewater containing the same levels of nitrogen and pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(38 citation statements)
references
References 61 publications
1
35
0
2
Order By: Relevance
“…As an illustration, it was previously reported that C. vulgaris could not use lactate for growth in mixotrophic conditions, and its presence was inhibitory to biomass growth . In contrast, the use of lactate by the same microalgal species was observed in heterotrophic conditions by Perez-Garcia et al (2011a). Therefore, the influence of lactate on biomass growth and on other substrates removal remains unclear for Chlorella sp.…”
Section: No Influence Of Lactate On Growthmentioning
confidence: 57%
“…As an illustration, it was previously reported that C. vulgaris could not use lactate for growth in mixotrophic conditions, and its presence was inhibitory to biomass growth . In contrast, the use of lactate by the same microalgal species was observed in heterotrophic conditions by Perez-Garcia et al (2011a). Therefore, the influence of lactate on biomass growth and on other substrates removal remains unclear for Chlorella sp.…”
Section: No Influence Of Lactate On Growthmentioning
confidence: 57%
“…Acetate, which can be derived from wastewater, is able to serve as an efficient carbon source for specific algae for heterotrophic cultivation [9]. Previous studies had demonstrated that the green microalga Scenedesmus obliquus was capable of assimilating acetate for biomass growth [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some research claims that microalgae do not have invertase to assimilate sucrose; then, others in contrast to them indicated positive results when using sucrose. For instance, Perez-Garcia et al (2011a) found that supplementation with sucrose, Ca-acetate and vinegar supported meagre multiplication of C. vulgaris, whilst the absence of a carbon source completely inhibited multiplication. In contrast, during research into hydrogen production by immobilised C. vulgaris, sucrose produced the greater amounts of hydrogen from all carbon sources (Rashid et al 2013).…”
Section: Removal Of Nitrate Without Addition Of External Carbon Sourcementioning
confidence: 99%
“…In accordance with the above reactions, carbon skeletons in the form of keto acids and energy in the form of ATP and NADH are required for this process (Perez-Garcia et al 2011a). Moreover, it was also reported that ammonium ions could interact with the carboxyl groups of the alginate beads (without microalgae) and chemically bound to it, which could also be reflected in the reduction of ammonium as they infiltrated continually through alginate into the cells (Ruiz-Marin et al 2010).…”
Section: Removal Of Ammonium In the Presence Of Nitratementioning
confidence: 99%
See 1 more Smart Citation